Amsterdam. - Miniature Book Society. Grand Conclave 2011 : Dublin, Ireland) ([Place of publication not identified] : [publisher not identified], 2011)
Given as a free gift at the Miniature Book Society Dublin Conclave 2011.
O.z. Voorburgwal -- Central Station -- Oude Schans M. Montelbeanstoren -- Postkantoor -- Hooge Sluis met Amstel-Hotel -- Rijks Museum -- Nieuwmarkt met Waag Gebouw -- Keizersgracht -- Dam met Kon. Paleis -- Munt. met Carlton Hotel -- Prins Hendrikkade.
Nine black and white photographs of Amsterdam, printed on paper, folded concertina style and attached to cover.
Keywords: Miniature books -- Specimens; Amsterdam (Netherlands) -- Buildings, structures, etc. -- Pictorial works